(untitled) (The Review of Diabetic Studies, 2024)
This narrative review explores nurses’ perspectives on the implementation of evidence-based practice (EBP) within their duties, highlighting the challenges and facilitators that influence its adoption. EBP is essential in contemporary nursing, as it integrates clinical expertise, patient preferences, and the best available evidence to enhance patient outcomes and improve care quality. Despite its significance, various barriers hinder successful EBP implementation, including insufficient knowledge, lack of organizational support, and cultural attitudes that favor traditional practices. Nurses often feel constrained by systemic issues, such as time limitations and inadequate training, which can lead to a reliance on anecdotal evidence rather than evidence-based guidelines. Conversely, several facilitators can enhance EBP implementation, including strong leadership support, access to educational resources, and mentorship programs. Creating a culture that values research and encourages inquiry is vital for promoting EBP among nursing professionals. Additionally, interprofessional collaboration can enhance understanding and application of EBP, leading to improved patient care outcomes. Education plays a crucial role in preparing nurses to engage with EBP effectively. Nursing curricula must emphasize EBP principles and provide practical experiences to bridge the gap between theoretical knowledge and real-world application. The review also emphasizes the positive impact of EBP on patient outcomes, including reduced complications and increased patient satisfaction, while highlighting the importance of ongoing evaluation and feedback to sustain EBP initiatives. Looking ahead, the future of EBP in nursing will be shaped by advancements in technology, such as electronic health records and clinical decision support systems, as well as the growing emphasis on interprofessional collaboration. By fostering a culture that values EBP, healthcare organizations can ensure that nurses are equipped to provide high-quality, evidence-based care, ultimately enhancing patient outcomes and the overall effectiveness of healthcare delivery.